HERMAPHRODITISM IN A TELEOST, POLYNEMUS HEPTADACTYLUS CUV. AND VAL. - Kagwade, P V (Indian Journal of Fisheries, 2011)
In fishes reproduction is normally sexual by fertilization of male and femalereproductive elements borne by individuals of the two separate sexes. However,certain reproductive specializations, viz. gynogenesis, parthenogenesis and hermaphroditismare at times met with. Gynogenesis is observed in Mollienesia formosa(Hubbs and Hubbs, 1932, 1946) which exclusively occurs as females, wherein duringreproduction the sperms of a related species only stimulate the eggs but do not contributeto any genetic material and the resulting offspring are all females. Gynogenesishas also been observed in a cyprinid fish Carassius auratus gibelio (Lieder,1955). Parthenogenesis or development of eggs without fertilization is very rare.Hermaphroditism, a condition in which both the male and female gametes are producedby the same individual, is very common in the lower animals but rare amongthe higher vertebrates. In teleosts it occurs either teratologically or normally or bythe reversal of sex. Herrings, cods, mackerels, sardines and some of the Pleuronectidaeexhibit teratological hermaphroditism. Some of the eels, symbranchids andmember? belonging to the families Maenidae, Sparidae and Serranidae are normallyhermaphrodites. A few members of these three families are subjected to sex reversal.Based on the nature of the ovotestis with respect to the maturing of the gamates,hermaphroditism can be classified into different groups. An ovotestis is said to begonochoritic when only one of its sexes functions at a time depending on whetherit is protandric or proterogynous. Self-fertilization is out of question here.D'Ancona (1945) has observed in Sparus auralies protandry where the male germcells mature earlier than those of the female and in Diplodus spp. and other sparids,the presence of both testicular and ovarian parts in the same gonad, but only one ofthem attaining maturity. This condition presents a transition from hermaphroditismand is considered primitive to gonochorism.